Apoteoza młodości w tekstach propagandowych z lat 1944-1956 - Ożóg, Sławomir (Słowo. Studia językoznawcze, 2015)
After the ending of the Second World War the communist authorities led intensive propaganda against Polish society. They paid a special attention to the youth. They applied against the young varied language strategies. One of the most interesting ones is presenting the youth as a value, its affirmation. The reconstruction of the linguistic representation of the youth in the propaganda texts shows not only this strategy, but also the full vision of the young person. The picture of the youth does not represent the real facts, it has rather postulate character, so it says about the future, the desired world. Despite this, it is presented as the reality already functioning. It is a typical manipulation technique for propaganda texts from this period.